PENGARUH KOMPETENSI, INDEPENDENSI DAN PERILAKU DISFUNGSIONAL AUDITOR TERHADAP KUALITAS AUDIT DI MODERASI OLEH RELIGIUSITAS : (Studi Empiris Pada Kantor Akuntan Publik Di Wilayah Jakarta Selatan) - Putri Tianingsih; Siti Hamidah Rustiana; Haris Sarwoko (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
This study aims to determine "The Effect of Auditor's Competence, Independence and Dysfunctional Behavior on Audit Quality in Moderation by Religiosity" (Empirical Study of Public Accounting Firms in South Jakarta). The type of research used is quantitative research with primary data sources. The population in this study is a public accounting firm in the South Jakarta area and the sample in this study are auditors who work at public accounting firms in the South Jakarta area. The number of samples in this study were 103 auditors. Quantitative data analysis was performed using the Partial Least Square (SEM-PLS) technique which was processed through the WarpPls 7.0 software. Based on the research results and the results of hypothesis testing, it shows that 1) competence has a positive and significant effect on audit quality, 2) independence has a positive and significant effect on audit quality, 3) dysfunctional behavior has a positive but insignificant effect on audit quality, 4) religiosity does not have a moderate effect competence on audit quality, 5) religiosity is not able to moderate the effect of independence on audit quality, 6) religiosity is not able to moderate the effect of auditor dysfunctional behavior on audit quality. Keywords: Competence, Independence, Auditor Dysfunctional Behavior, Religiosity